Raden Ranggawarsita's Correction of the Javanese Islamic Calendar in Serat Widyapradhana - Mufidah, Kurnia Sofi (Universitas Islam Negeri Sumatera Utara, 2025)
The Javanese Islamic calendar is a cultural heritage passed down from our ancestors that continues to be preserved today. Some communities still use it in their daily lives. However, not everyone pays close attention to the correction system required for its proper use. Ranggawarsita, a prominent figure of the royal court, wrote a manuscript titled Serat Widyapradhana, which offers a detailed explanation of the application of the Javanese Islamic calendar, including how corrections should be made. This study uses a descriptive qualitative approach to explain how Raden Ranggawarsita addressed the correction system within the Javanese Islamic calendar. Data was collected through library research, using the Serat Widyapradhana manuscript as the main source. A philological approach was applied to help the researcher better understand the text. The study found, first, that the Javanese Islamic calendar was already in use before the reign of Sultan Agung, particularly by Sunan Giri II. Second, Ranggawarsita explained in his writings how corrections should be made to the calendar, especially regarding the 2400-year kurup cycle, to prevent the calendar from falling out of sync. These corrections are essential to maintain harmony between the Islamic Hijri calendar and the Javanese calendar. This research highlights the need for greater awareness and understanding among users of the Javanese Islamic calendar, encouraging deeper engagement with the system and contributing to the broader field of Islamic astronomy, particularly in the study of calendar variations.